2011
DOI: 10.1002/bies.201100094
|View full text |Cite
|
Sign up to set email alerts
|

Cdc20 control of cell fate during prolonged mitotic arrest

Abstract: The fate of cells arrested in mitosis by antimitotic compounds is complex but is influenced by competition between pathways promoting cell death and pathways promoting mitotic exit. As components of both of these pathways are regulated by Cdc20-dependent degradation, I hypothesize that variations in Cdc20 protein levels, rather than mutations in checkpoint genes, could affect cell fate during prolonged mitotic arrest. This hypothesis is supported by experiments where manipulation of Cdc20 levels affects the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…FACS analysis of the tagged SUMO2 cell line revealed that this synchronization protocol resulted in a G2/M arrest (Figure S1A and Materials and Methods S1) and visual inspection of cells by microscopy revealed that they were arrested in prometaphase. The addition of taxol to the medium arrests cells in prometaphase by activating the spindle assembly checkpoint [26]. A very efficient and synchronous mitotic exit was achieved from taxol-arrested cells by inhibition of Aurora B with ZM447439 [27], as revealed by the rapid disappearance of Cyclin B1 and Aurora A already one hour after inhibitor addition (Figure 2B).…”
Section: Resultsmentioning
confidence: 96%
“…FACS analysis of the tagged SUMO2 cell line revealed that this synchronization protocol resulted in a G2/M arrest (Figure S1A and Materials and Methods S1) and visual inspection of cells by microscopy revealed that they were arrested in prometaphase. The addition of taxol to the medium arrests cells in prometaphase by activating the spindle assembly checkpoint [26]. A very efficient and synchronous mitotic exit was achieved from taxol-arrested cells by inhibition of Aurora B with ZM447439 [27], as revealed by the rapid disappearance of Cyclin B1 and Aurora A already one hour after inhibitor addition (Figure 2B).…”
Section: Resultsmentioning
confidence: 96%
“…APC/C forms a protein complex with its mitotic coactivator, CDC20, which controls mitotic progression [59]. CDC20 protein level may directly affect cell fate during prolonged mitotic arrest [60] and its turnover rate may be a key factor in cancer patient response to antimitotic therapies [61]. …”
Section: Resultsmentioning
confidence: 99%
“…Previously, Nilsson (2011) has suggested that the level of Cdc20 might be one of the key features determining response to anti-mitotic cancer therapeutics. Downregulation of Cdc20 in breast cancer cells has been associated with inhibition of cell proliferation in vitro (Jiang et al , 2011, 2012).…”
Section: Discussionmentioning
confidence: 99%